Biomagnetic Fluid Flow on a Nonlinearly Stretching Sheet with Variable Thickness in a Magnetic Environment - Murtaza, Md. Ghulam; Misra, Jagadis C.; Tzirtzilakis, Efstratios E.; Ferdows, Mohammad (Journal of Advances in Applied & Computational Mathematics, 2023)
The main contribution of the current work is a numerical and mathematical investigation of the effects of magnetic dipole and electrical conductivity on the heat and flow transfer of biomagnetic fluid over a non-linear stretched sheet with variable thickness. Static magnetic fields are produced by magnetic dipoles, which are used in medical a pplications such as MRI, drug administration, and cancer therapy. Additionally, the impact of non-linear heat source/sink features was examined in the study, leading to an interesting phenomenon. The PDEs are attenuated to nonlinear ODEs with dealing appropriate similarity variables. These resultant ODEs are computed by developing an effective method emerged on the application of the finite differences technique. In the end, this section offers a summary of the implications resulting from different physical limitations on blood flow, including variable thickness and power index effects. It was discovered that the rise in Kelvin and Lorentz forces in the boundary layer significantly affected blood flow. The current findings for the biomagnetic fluid model are novel and inventive since they effectively expand upon the issues previously addressed by previously published scientific documentation.